OPTIMASI EKSTRAKSI DAN PENENTUAN KANDUNGAN KATEKIN DALAM TEH HIJAU (Camellia sinensis) MENGGUNAKAN METODA HPLC - sudjatini, Sudjatini (Universitas Widya Mataram, 2017)
Â This research was designed to determine the optimum period extraction time for catechin green tea using boiling water and ethyl acetate as a solubilizing agent, whereas the composition and the content of catechin green tea were measured using High Performance Liquid Chromatography (HPLC). A single factor experiment design was used. The period extraction time of green tea using boiling water and ethyl acetate were 5, 20, 35 and 60 minutes. The proportion of green tea at the extraction process was 1:15 (weight/volume). The extraction process using boiling water was done twice to get the maximum extracted catechin yield. The extracted catechin of green tea were, therefore, compared with epi-catechin as standard solution. The researchâ€™s results show that the optimum period for extraction time of green tea using boiling water and ethyl acetate were 35 and 20 minutes, respectively. The extracted green tea using boiling water was 41.39 % of its dry weight, and those extracted green tea contained catechin as high as 60.62-61.78 %. Catechin compound in green tea residues extracted using ethyl acetate was 5.31 % from 58.35 % the total green tea residues. The composition of catechin in the first boiling water extraction, the second boiling water extraction and pressure extraction consisted of epigallocatechin (EGC), epigallocatechin-gallat (EGCG), epicatechin (EC) and epicatechin-gallat (ECG). ECG was only found in green tea residue extracted using ethyl acetate. The total catechin compound in green tea extracted using boiling water and ethyl acetate was 27.73 % of dry weight, consisted of EGC, EGCG, EC and ECG were 14.74, 1.73, 8,35 and 2.91 % of green tea dry weight, respectively